AB0176 Pulmonary Assessment in Acpa Positive Subjects without Inflammatory Arthritis and in Patients with Early and Established Rheumatoid Arthritis: The Role of Functional and Inflammatory Biomarkers. (15th July 2016) - Iannuccelli, C.; Gerardi, M.C.; Di Paolo, M.; Bonini, M.; Vomero, M.; Lucchino, B.; Palange, P.; Di Franco, M.; Valesini, G.
Abstract : Background: It is known that citrullinated proteins (ACPA) may be present years before the onset of clinical manifestations of Rheumatoid Arthritis (RA). Recent findings suggest that the lung may represent an early site of autoimmune-related injury in ACPA-positive patients without signs of arthritis (1, 2). Objectives: The purpose of the present study was to evaluate the presence of subclinical pulmonary abnormalities in ACPA-positive subjects without arthritis and in RA-patients through functional and inflammatory biomarkers. Methods: Thirty consecutive patients: 11 ACPA-positive without arthritis, 10 naïve to therapy with early ACPA-positive RA (<24 weeks) and 9 with established ACPA-positive RA (<36 months duration) were enrolled. After obtaining informed consent, all subjects underwent baseline pulmonary function tests (PFTs), DLCO measurement and cardiopulmonary exercise testing (CPET). A blood sample for the ELISA evaluation of Surfactant protein D (SP-D) serum levels was collected. Serum levels of SP-D were also measured in 9 healthy control age and sex-matched. Exclusion criteria were: cardiovascular disease, lung disease already known, diabetes, other autoimmune diseases Results: The cohort consisted of 7 men and 23 women, mean age 48, 93 (DS ±12.1). PFTs resulted abnormal only in 2 patients. A DLCO reduction was observed in 54.5% of ACPA-positive subjects without RA, in 60% and in 55.6% of patients with early and established RA, respectively. In RA patients, an inverse correlation between disease duration and ratio of the diffusing capacity to the alveolar volume (DLCO/Va) (r=-0.50; p=0.03) was observed. The exercise tolerance (V'O2 peak) at CPET was reduced in 54.5% of ACPA-positive subjects without RA, in 20% of patients with early RA and in 55.6% of those with established RA. Serum levels SP-D were higher in established RA (p=0.079) and in ACPA-positive subjects and early RA than in healthy control. Interestingly enough, ACPA levels positively correlated (r=0.45; p=0.01) with CPET parameters of ventilatory inefficiency (ratio of the increase in ventilation (V'E) to the increase in CO2 output (V'CO2) at lactic threshold (LT)-V'E/V'CO2@LT), suggesting a ventilation/perfusion mismatch. A negative correlation between ACPA and SP-D levels and CPET metabolic parameters (oxygen uptake (V'O2)) was also observed (SP-D-V'O2@LT/kg r=-0.38 p=0.03 – V'O2@LT/kg-ACPA r=-0.36 p=0.05). Conclusions: The lung involvement in RA, particularly in the early phases of disease, is often subclinical and baseline PFTs are scarcely informative. Although preliminary, these findings suggest that DLCO, CPET parameters and SP-D can represent early markers of the subclinical lung injury. Additional studies are however needed to clarify lung abnormalities in RA. References: Demoruelle et al. Annals of the Rheumatic Diseases 2012 Valesini et al. Autoimmunity Review 2015 Disclosure of Interest: None declared